Evaluation of the gender effect in operated prolactinomas - Özaydın, Dilan; Demir, Ahmet Numan; Tanrıöver, Necmettin (The European Research Journal, 2023)
Objectives: To investigate the differences between the characteristics of disease presentation and treatment outcomes on the basis of gender in patients with operated prolactinoma. Methods: Prolactinoma patients who underwent endoscopic transsphenoidal surgery at Istanbul University-Cerrahpasa, Neurosurgery clinics between 2013-2023 were included in this study. Surgical indications, secondary treatments, clinical, demographic, biochemical, radiological findings, and pathological data were analyzed. Data were compared between the gender groups. Results: Thirty-two men and 28 women were included in the study. The mean age of the men was 44 years and that of the women was 29 years. While men were more likely to have decreased libido, women were more likely to have menstrual irregularities (p < 0.001). The tumor was larger in men (p = 0.001), presenting with a more frequent suprasellar invasion (p = 0.001) and cavernous sinus invasion (p < 0.001). Pituitary hormone deficiency (p < 0.001) and visual field defects (p < 0.001) occurred more frequently in men. Conclusions: Male prolactinoma patients tend to have more invasive and larger tumors. Men are less likely than women to go into remission with surgery. This difference in presentation may be due to indistinct symptoms in male patients and late diagnosis.